Promoting The Development Of Improved Cleaning Technology - Azizbek Rakhimjonov; Ugiloy Bakhtiyorova (Genius Journals, 2023)
Improving product quality and maintaining its quality indicators as a result of reducing the cost of cleaning machines and increasing their efficiency due to the introduction of improved technologies into production information about
Keywords: stewardship; impurities; seed cotton; cleaning machines